Inflammatory breast cancer (IBC): clues for targeted therapies - Fernandez, Sandra V.; Robertson, Fredika M.; Pei, Jianming; Aburto-Chumpitaz, Lucy; Mu, Zhaomei; Chu, Khoi; Alpaugh, R. K.; Huang, Yong; Cao, Yu; Ye, Zaiming; Cai, Kathy Q.; Boley, Kimberly M.; et al. (Breast cancer research and treatment, 2013)
Inflammatory breast cancer (IBC) is the most aggressive type of advanced breast cancer characterized by rapid proliferation, early metastatic development and poor prognosis. Since there are few preclinical models of IBC, there is a general lack of understanding of the complexity of the disease. Recently, we have developed a new model of IBC derived from the pleural effusion of a woman with metastatic secondary IBC. FC-IBC02 cells are triple negative and form clusters (mammospheres) in suspension that are strongly positive for E-cadherin, β-catenin and TSPAN24, all adhesion molecules that play an important role in cell migration and invasion. FC-IBC02 cells expressed stem cell markers and some, but not all of the characteristics of cells undergoing epithelial mesenchymal transition (EMT). Breast tumor FC-IBC02 xenografts developed quickly in SCID mice with the presence of tumor emboli and the development of lymph node and lung metastases. Remarkably, FC-IBC02 cells were able to produce brain metastasis in mice on intracardiac or intraperitoneal injections. Genomic studies of FC-IBC02 and other IBC cell lines showed that IBC cells had important amplification of 8q24 where MYC, ATAD2 and the focal adhesion kinase FAK1 are located. MYC and ATAD2 showed between 2.5 and 7 copies in IBC cells. FAK1, which plays important roles in anoikis resistance and tumor metastasis, showed 6–4 copies in IBC cells. Also, CD44 was amplified in triple-negative IBC cells (10–3 copies). Additionally, FC-IBC02 showed amplification of ALK and NOTCH3. These results indicate that MYC, ATAD2, CD44, NOTCH3, ALK and/or FAK1 may be used as potential targeted therapies against IBC.